Unemployment Problems in Indonesia - Islami, Fiqri Hadi; Nurshahila, Irma (Program Pascasarjana, Universitas Riau, 2025)
This study examines the issue of unemployment in Indonesia, which remains one of the major challenges in national economic development. The purpose of this research is to analize the factors causing unemployment, its socio-economic impacts, and the strategies that can be implemented by the government to address it. The research employs a qualitative descriptive approach using literature study, based on secondary data from the Badan Pusat Statistik (BPS), scientific journals, and previous studies from 2020–2025. The findings indicate that unemployment in Indonesia is multidimensional, influenced by imbalances between economic growth and labor absorption, low human resource quality, and the mismatch between education and industrial needs. Moreover, unequal investment distribution and minimum wage policies have worsened the situation. Unemployment has broad impacts, including rising poverty, social inequality, and declining welfare. Therefore, comprehensiveness is needed focusing on skill development, labor-intensive investments, and synergy among government, businesses, and educational institutions to achieve inclusive and sustainable economic growth in Indonesia.